2007
DOI: 10.1111/j.1753-6405.2007.00113.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of opioid replacement pharmacotherapy in an urban Aboriginal Health Service

Abstract: Objective: This study aimed to evaluate the opioid replacement pharmacotherapy at Winnunga Nimmityjah Aboriginal Health Service (Winnunga) in the Australian Capital Territory. Methods: Existing and new adult patients at Winnunga who were receiving opioid replacement pharmacotherapy were recruited. Twenty‐one of 30 eligible patients participated in this cohort study. The Brief Treatment Outcome Measure was administered to patients twice with an interval of at least three months. Primary outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 16 publications
1
23
0
Order By: Relevance
“…Similar findings have been observed among Aboriginal people in studies of people who inject drugs in Canada [23]. In contrast, an evaluation of OST provision in an urban Australian Aboriginal Health Service found that rates of treatment retention and heroin use reduction were equivalent to those observed in mainstream treatment programs [24]. There is therefore a clear need for further research to resolve these differences in study findings, given the potential benefits of treatment in this population.…”
Section: Introductionsupporting
confidence: 57%
“…Similar findings have been observed among Aboriginal people in studies of people who inject drugs in Canada [23]. In contrast, an evaluation of OST provision in an urban Australian Aboriginal Health Service found that rates of treatment retention and heroin use reduction were equivalent to those observed in mainstream treatment programs [24]. There is therefore a clear need for further research to resolve these differences in study findings, given the potential benefits of treatment in this population.…”
Section: Introductionsupporting
confidence: 57%
“…Since these earlier studies, culturally-centered MAT services have been successfully implemented with Indigenous people in Australia and Canada (1921). In Australia, success was attributed to the culturally-specific design, integrated care, and a focus on family and community wellness (21).…”
Section: Pharmacological Treatment Of Opioid Use Disorder With Ai/ansmentioning
confidence: 99%
“…Pharmacy data, observational study data and randomised control trials of Indigenous people suggest that Indigenous people are prescribed and tolerate medications for mental disorders at similar rates to non-Indigenous people [5862]. The pharmacoepidemiology sections of the CIDI ask about the use of prescription and non-prescription medications (usually in the past 12 months) for mental health and substance use reasons, professional supervision, duration of use and adherence [18].…”
Section: Discussionmentioning
confidence: 99%